Características de adsorção de fósforo em alguns solos da Amazônia Central - Falcão, Newton Paulo de Souza; Silva, José Risonei Assis da (Acta Amazonica, 2004)
The objective of this paper was to determine the phosphorus adsorption characteristics using the Langmuir isotherm and it is relation with some physical and chemical properties of soils. The study was carried out in the Soil and Plant Laboratory, of the National Institute for Amazon Research (INPA), Brazil, with surface (0-20 cm) samples from eight soils of the Amazonas State. Ample variation of the maximum phosphorus capacity factor (MPAC), adsorption energy and maximum phosphorus capacity factor (PmCF) were observed. The Plinthite soil showed the highest values of the MPAC and PmCF and the Yellow Oxisol 1 (LAx-1) showed the highest adsorption energy. The MPAC ranged from 0.297 to 0.888 mg P g-1 of soil, the adsorption energy with which the phosphorus is sorbed was between 0,230 and 0,730 L mg-1, and the PmCF. ranged from 137 to 593 mL g-1. The PmCF decreased from Plinthite (FTa) > Yellow Oxisol (LAx-1) > Yellow Oxisol (LAx-3) > Yellow Oxisol (LAx-6) > Yellow Oxisol (LAx-2) > Yellow Oxisol (LAx 4) > Yellow Ultisol (PAd) > Yellow Oxisol (LAx-5). The MPAC and the PmCF were positively correlated with clay content (r = 0,948** e r = 0,962** ) and exchangeable Al3+ (r = 0,688* e r = 0,666* ), and negatively correlated with base saturation (r = - 0,667* e r = - 0,761*), respectively. The adsorption energy was positively correlated with clay content (r = 0,783*) and negatively with base saturation (r = - 0,775*).
Phosphorus adsorption characteristics in some Central Amazonian soils
Keywords: Phosphorus Fixation; Tropical Soils; Amazon; Fixação De P; Solos Tropicais; Amazônia